Elasticity of Demand and Stabilisation - Makower, Helen (Review of Economic Studies, 1938)
Journal Article Elasticity of Demand and Stabilisation Get access Helen Makower Helen Makower Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 1, October 1938, Pages 25–32, https://doi.org/10.2307/2967536 Published: 01 October 1938